Perception of health-related quality of life, sleep quality and sleepiness index in an educational environment at a dental school in Southeast Brazil - Caldeira, François Isnaldo Dias [UNESP]; Cardoso, Bruna; Carvalho, Leonardo de Souza; Batista Ferreira, Eric; Pigossi, Suzane Cristina; Rodriguez, Larissa Santana (Wiley, 2021)
Introduction: University entrance is often associated with changes in quality of life, individuals' cognitive and physical behavior. The present study aimed to evaluate health-related quality of life (HRQoL), sleep quality and sleepiness index in dentistry students at a university in Southeast Brazil, in different semesters of their course. Materials and methods: Samples were obtained from 55 students from the dentistry course at the Federal University of Alfenas (UNIFAL-MG). For collecting information, validated SF-36 questionnaires (Medical Outcomes Study 36-item Short-Form Health Survey), namely, Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS), were used as instruments in an educational environment. The relationship between the association of demographic factors and academic performance with SF-36, PSQI and ESS was assessed with an alpha of 0.05. Results: The worst HRQoL parameters reported by the participants were observed in the domains of body pain, vitality, general health perception, and limitations due to emotional and social aspects when associated with the investigated variables. Regarding the relative sleep quality index, differences in the PSQI domains were observed when related to demographic factors and academic performance. There was no significant difference in the sleepiness index of these students according to the mean values of the ESS domains. Conclusion: The SF-36, PSQI and ESS questionnaires indicated that it is a reliable instrument for measuring the impact of quality of life on dentistry students. In addition, dentistry students of UNIFAL-MG had poor indicators of quality of life associated with health and an inadequate index of quality of sleep.